Left Ventricular Myocardial Function in a Cat with Nonspecific Cardiomyopathy Phenotype - Barbosa, Thaís Gomes; Coelho, Mariana de Resende; Muzzi, Ruthnea Aparecida Lázaro; Pereira, Ana Flávia Silva; Oliveira, Luiz Eduardo Duarte de; Abreu, Claudine Botelho de (Acta Scientiae Veterinariae, 2020)
Background: Non-specific phenotype feline cardiomyopathy (CFNE) is one that does not fit properly in the other categories, and it is necessary to describe in detail the morphology and cardiac function. The causes of CFNE is not very clear, and it may be due to congenital or acquired disease, or also to primary or secondary myocardial dysfunction associated with other conditions. In symptomatic cases, the clinical signs observed are compatible with left congestive heart failure (ICCE). This study reports a CFNE case in an asymptomatic cat, in order to demonstrate the importance of echocardiographic examination in the early diagnosis of the disease. Case: A 6.5-year-old non-neutered crossbred cat weighing 3.1 kg was seen at the institution’s veterinary hospital for routine cardiac evaluation. No clinical signs were reported in the history. On physical examination, the animal presented calm behavior, body score 5/9, heart rate 200 bpm, systolic blood pressure of 102 mmHg, respiratory rate 64 mrp, and other normal parameters. CBC and urinalysis laboratory tests were requested, which were unchanged. The electrocardiogram showed normal patterns. In the conventional echocardiographic examination, a significant increase in the left atrium (LA) was observed, and the LA/Ao ratio was 2.05 and the diastolic function was abnormal. There was no presence of concentric hypertrophy of the left ventricle (LV), the thickness of the ventricular wall measured at different points, in the two-dimensional mode and the M mode, was less than 5 millimeters. Other parameters of conventional echocardiography were within the normal range. Through these echocardiographic findings, the suggestive diagnosis was non-specific phenotype cardiomyopathy, with a significant increase in LA. For the assessment of left ventricular myocardial deformation, the strain (St%) and strain rate (StR 1/s) indexes (which correspond to the percentage and speed at which the myocardial fiber deforms during the cardiac cycle, respectively) were evaluated using two-dimensional feature tracking (2D-FTI), with the aid of Xstrain version 10.1 software, optical flow algorithm (ESAOTE®). This analysis showed a decrease in the overall value of the longitudinal and radial St/StR variables. Discussion: The CFNE echocardiographic examination can demonstrate several structural cardiac changes that are not characterized in any other category of cardiomyopathy. Although the patient is still asymptomatic, the echocardiogram made it possible to identify structural changes compatible with the reported disease (enlargement of the left atrium and left ventricular myocardial deformation). Using the 2D-FTI technique, the vulnerability of the myocardial fibers in the longitudinal and radial directions of the left ventricle was observed, demonstrating that despite the patient still not showing clinical signs, there were already signs of ventricular dysfunction. These changes observed by the 2D-FTI technique, suggest that the patient may develop clinical signs of ICCE, resulting from pleural effusion and/or pulmonary edema, requiring more frequent reassessments. For this reason, animals with CFNE should undergo periodic cardiac evaluation to monitor the evolution of the patient’s clinical condition. The use of more specific tools, such as 2D-FTI, allows an earlier assessment of clinical changes, which provides a faster therapeutic intervention when necessary, preventing the patient from abruptly decompressing.